The categories of violation of the right to life by security forces in the Inter-American Court of Human Rights and the European Court of Human Rights - Kaliman Sabrina Judith (Comparative Law Working Papers, 2022)
The regional courts of human rights have been condemning the violations to these rights for a long time. The right to life is the right that must be protected to guarantee the other human rights. Nevertheless, the right to life is violated by security forces of the states that are supposed to protect this one. For this the European Court of Human Rights and the InterAmerican Court of Human Rights issue judgments to condemn the violation of this right by these forces. The Inter-American Court of Human Rights and the European Court of Human Rights has established several judgments about the right to life in relation with different violations of this one. This work will seek to answer the interrogative of which are the different categories of violations of the right to life by security forces of the State in the European Court of Human Rights and the Inter-American Court of Human Rights. The categories were established through examples of judgments and case-law of the InterAmerican Court of Human Rights and the European Court of Human Rights. This work enumerates five categories that is not exhaustive because there can be more classifications, sub-categories or several categories may overlap.